2021
DOI: 10.1155/2021/5514175
|View full text |Cite
|
Sign up to set email alerts
|

Huang-Pu-Tong-Qiao Formula Ameliorates the Hippocampus Apoptosis in Diabetic Cognitive Dysfunction Mice by Activating CREB/BDNF/TrkB Signaling Pathway

Abstract: Background. Huang-Pu-Tong-Qiao formula (HPTQ), a traditional Chinese medicine (TCM) formula used to improve cognitive impairment. However, the underlying neuroprotective mechanism of HPTQ treated for diabetic cognitive dysfunction (DCD) remains unclear. The purpose of this study was to investigate the neuroprotective mechanism of HPTQ in DCD mice based on molecular docking. Methods. To investigate the neuroprotective effect of HPTQ in DCD, the Morris water maze (MWM), novel object recognition (NOR) test was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The activation of CREB by phosphorylation is required for long-term memory formation [ 69 ]. Furthermore, CREB phosphorylation upregulates the expression of BDNF [ 70 ]. In our study, the upregulated p-CREB/CREB ratio demonstrated the association between BDNF and CREB.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of CREB by phosphorylation is required for long-term memory formation [ 69 ]. Furthermore, CREB phosphorylation upregulates the expression of BDNF [ 70 ]. In our study, the upregulated p-CREB/CREB ratio demonstrated the association between BDNF and CREB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CREB pathway positively affects cognitive health, neuronal survival, neurogenesis, synaptic plasticity, and general neuronal activation. In this regard, polyphenols can bind to the estrogen receptor (ER) and activate neurotrophic effects through protein kinase C (PKC) pathways (path-way 2 in Figure 3 ) [ 13 , 23 , 27 , 70 , 78 , 82 , 83 , 84 , 85 ].…”
Section: Polyphenols In the Nervous System And Their Neuroprotective ...mentioning
confidence: 99%
“…Another neuroprotective effect of polyphenols in the brain is the elimination of ROS. Polyphenols induce an antioxidant effect by activating protein kinases that signal molecular pathways, such as Keap1/Nrf-2/ARE, the main protection pathways against endogenous and exogenous ROS [ 84 , 85 , 86 ]. Polyphenols interact and activate receptor kinases ERK1/2, JNK, and p38 protein, to disrupt the Keap1/Nrf2 complex and allow the translocation of nuclear factor 2 (Nrf2)-related transcription factor to the nucleus, where it binds to receptors rich in adenylate and uridylate (ARE), and promotes the expression of antioxidant proteins and enzymes (GSH, GST, GPX, SOD, and CAT) (path-way 3 in Figure 3 ).…”
Section: Polyphenols In the Nervous System And Their Neuroprotective ...mentioning
confidence: 99%